TaNAC1 acts as a negative regulator of stripe rust resistance in wheat, enhances susceptibility to Pseudomonas syringae, and promotes lateral root development in transgenic Arabidopsis thaliana - Wang, Fengtao; Lin, Ruiming; Feng, Jing; Chen, Wanquan; Qiu, Dewen; Xu, Shichang (Frontiers in Plant Science, 2015)
Plant-specific NAC transcription factors constitute a large family and play important roles in regulating plant developmental processes and responses to environmental stresses, but only some of them have been investigated for effects on disease reaction in cereal crops. Virus-induced gene silencing (VIGS) is an effective strategy for rapid functional analysis of genes in plant tissues. In this study, TaNAC1, encoding a new member of the NAC1 subgroup, was cloned from bread wheat and characterized. It is a transcription factor localized in the cell nucleus, and contains an activation domain in its C-terminal. TaNAC1 was strongly expressed in wheat roots and was involved in responses to infection by the obligate pathogen Puccinia striiformis f. sp. tritici and defense-related hormone treatments such as salicylic acid, methyl jasmonate and ethylene. Knockdown of TaNAC1 with barley stripe mosaic virus-induced gene silencing (BSMV-VIGS) enhanced stripe rust resistance. TaNAC1-overexpression in Arabidopsis plants gave enhanced susceptibility, attenuated systemic-acquired resistance to Pseudomonas syringae DC3000, and promoted lateral root development. Jasmonic acid-signaling pathway genes PDF1.2 and ORA59 were constitutively expressed in transgenic plants. TaNAC1 overexpression suppressed the expression levels of resistance-related genes PR1 and PR2 involved in SA signaling and AtWRKY70, which functions as a connection node between the JA- and SA-signaling pathways. Collectively, TaNAC1 is a novel NAC member of the NAC1 subgroup, negatively regulates plant disease resistance, and may modulate plant JA- and SA-signaling defense cascades.